The COVID-19 Pandemic in the IGAD Region: Consequence and Responses - Redie Bereketeab (Britain International for Academic Research (BIAR-Publisher), 2021)
This article examines the consequences of COVID-19 pandemic in the Intergovernmental Authority on Development (IGAD) region. In its epidemiological, as well as socio-economic dimensions, the pandemic presents extraordinary difficulties. The states in the region already suffer of dearth of basic medical equipment, medicines, personnel, health infrastructures and other health related materials. Early on, it also became clear that the Western world would not extend helping hand, in particular, with regard to crucially needed medical equipment and masks. The European Union’s decision not to sell medical equipment outside the bloc sent a clear signal that the region is on its own. Releasing this the governments of the region focused on measures of prevention. They, while on the one hand introduced severe lockdown, state of emergency and curfews, and on the other began to mobilise their social capital. The consequences of the total lockdown are yet to be properly assessed; however, socio-economic impacts are already immense. The article argues that dealing with the consequences of the pandemic requires pulling together all the resources of the region that depend on effective and coherent mobilisation and organisation of resources, capacities and social capital.